Pertimbangan Hakim yang memberikan Hak Asuh Anak yang Belum Mumayyiz kepada Ayah Kandung dalam Putusan Pengadilan Agama Tanjung Karang Nomor: 1379/Pdt.G/2024/PA.Tnk - Cynara Alya Zhafirah; Nunung Rodliyah; Kasmawati Kasmawati; Elly Nurlaili; Sayyidah Sekar Dewi Kulsum (Pusat Riset dan Inovasi Nasional, 2026)
This study discusses the judge’s considerations in granting child custody of a non-mumayyiz (underage) child to the biological father in the Religious Court Decision of Tanjung Karang Number: 1379/Pdt.G/2024/PA.Tnk. Generally, according to Islamic law and the Compilation of Islamic Law (KHI), custody of a non-mumayyiz child is granted to the biological mother. However, in this case, the panel of judges decided to grant custody to the biological father. The purpose of this research is to identify the legal reasoning behind the judge’s decision and the legal implications of such a ruling. The study employs a normative juridical method with a descriptive-analytical approach, supported by primary data obtained through interviews and secondary data from legislation and legal literature. The results show that the judge’s consideration was based on the best interest of the child principle, as the mother had remarried a non-Muslim man and converted to another religion, which made her ineligible to be the custodian under Islamic law. The legal implication of this decision reinforces the authority of judges to interpret hadhanah provisions contextually, ensuring the protection of the child’s rights and supporting their growth in accordance with religious teachings and prevailing social norms.